Show that :- (3x+7)² - 84 x = ( 3x – 7)²
Answers
Answered by
9
To Prove :-
(3x + 7)² – 84 x = (3x – 7)²
Proof :-
➨ (3x + 7)² – 84x = (3x – 7)²
Use Identities :-
• (a + b)² = a² + b² + 2ab.
• (a – b)² = a² + b² – 2ab.
➨ (3x)² + 7² + (2)(3x)(7) – 84x = (3x)² + 7² – (2)(3x)(7).
➨ 9x² + 49 + 42x – 84x = 9x² + 49 – 42x.
➨ 9x² + 49 – 42x = 9x² + 49 – 42x.
Use Transposition.
➨ 9x² – 9x² – 42x + 42x = 49 – 49.
➨ 0 = 0.
LHS = RHS.
Hence, Verified.
Some Identities to Remember :-
- (a + b)² = a² + b² + 2ab.
- (a – b)² = a² + b² – 2ab.
- (a)² – (b)² = (a + b)(a – b).
Answered by
0
Answer:
here is your answer
mark me as brainlist.....
Attachments:
![](https://hi-static.z-dn.net/files/d42/4aa43fc714e9124c3797098887b66c4e.jpg)
Similar questions
Political Science,
3 months ago
Social Sciences,
3 months ago
Social Sciences,
7 months ago
History,
1 year ago
Math,
1 year ago